2020
DOI: 10.12928/dpphj.v14i2.2027
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Suicide in Gunungkidul Indonesia

Abstract: Background: The suicide incidents in Gunungkidul did not decrease according to previous reports. This research was conducted to described suicide trends in Gunungkidul from 2012 to 2019 and their characteristics. Method: The research used retrospective approach by analyzing suicide data from local police based on demography (sex, occupation, age, residence) and the methods of suicide. We analyzed the suicide trends in the last 8 years. Results: The result of the descriptive analysis shows that suicide in Gunun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…Several reports have estimated the prevalence of suicide in Gunungkidul to exceed the national trend. 2,3 Several parties have proposed explanations and factors behind the high number of suicides in Gunungkidul, such as poverty and social change, distortion of meaning applied to the belief of "pulung gantung", mental health issues, and to the absence of adequate resources. 17,18,19,21 This study was conducted to estimate the effect of the COVID-19 pandemic on suicide patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several reports have estimated the prevalence of suicide in Gunungkidul to exceed the national trend. 2,3 Several parties have proposed explanations and factors behind the high number of suicides in Gunungkidul, such as poverty and social change, distortion of meaning applied to the belief of "pulung gantung", mental health issues, and to the absence of adequate resources. 17,18,19,21 This study was conducted to estimate the effect of the COVID-19 pandemic on suicide patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study found a limited difference in trends, this change may be a manifestation of random patterns as in previous studies. 3 This study also analyzes limited data and also influences the level of sensitivity of predictive patterns. In addition, this article does not reveal whether the decline in the trend of suicide is also accompanied by a decrease in suicidal ideation or the attempts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bunuh diri dianggap sebagai mekanisme penegakkan harga diri atas rasa malu (Crowder & Kemmelmeier, 2018). Wirang inilah yang oleh beberapa kalangan disebut sebagai faktor risiko tindakan bunuh diri di Jawa (Darmaningtyas, 2002;Nurdiyanto & Jaroah, 2020). Meski demikian, perlu dilakukan kajian lebih lanjut untuk menggali makna wirang dalam kaitannya dengan bunuh diri.…”
Section: Pembahasanunclassified